Determination of the strain distribution for the Si3N4 passivated AlGaN/AlN/GaN heterostructure field-effect transistors. (November 2017) - Fu, Chen; Lin, Zhaojun; Liu, Yan; Cui, Peng; Lv, Yuanjie; Zhou, Yang; Dai, Gang; Luan, Chongbiao
Abstract: A method to determine the strain distribution of the AlGaN barrier layer after the device fabrication and the passivation process has been presented. By fitting the calculated parasitic source access resistance with the measured ones for the AlGaN/AlN/GaN HFETs and using the polarization Coulomb field scattering theory, the strain variation of the AlGaN barrier layer after the passivation process has been quantitatively studied. The results show that the tensile strain in the access regions of the AlGaN barrier layer has been increased by 4.62% for the 250 nm-Si3 N4 passivated device, and has been decreased by 2.0% for the 400 nm-Si3 N4 passivated device, compared to that of before the passivation, respectively. For the gate region of the two devices, the tensile strain has been decreased by 60.77% and increased by 3.60% after the passivation of different thicknesses, oppositely. Highlights: The strain distribution of the AlGaN barrier layer after passivation in the AlGaN/AlN/GaN HFETs is determined. The tensile strain in the access regions is intensified or weakened by different thicknesses of passivation. The change of the PCF scattering is the main reason for the variation of the strain after passivation.